Ochrobactrum daejeonense sp. nov., a nitrate-reducing bacterium isolated from sludge of a leachate treatment plant - Woo, Sung-Geun; Ten, Leonid N.; Park, Joonhong; Lee, Myungjin (International Journal of Systematic and Evolutionary Microbiology, 2011)
A Gram-reaction-negative, non-spore-forming, rod-shaped, aerobic bacterial strain, designated MJ11T, was isolated from sludge of a leachate treatment plant in Daejeon, South Korea, and was characterized taxonomically by using a polyphasic approach. Comparative 16S rRNA gene sequence analysis showed that strain MJ11T belonged to the family Brucellaceae, class Alphaproteobacteria, and was most closely related to Ochrobactrum ciceri Ca-34T (97.9 % sequence similarity) and Ochrobactrum pituitosum CCUG 50899T (96.4 %). Comparative sequence analyses of the additional phylogenetic marker genes dnaK, groEL and gyrB confirmed the affiliation of strain MJ11T to the genus Ochrobactrum. The G+C content of the genomic DNA of strain MJ11T was 59.3 mol%. The detection of a quinone system with ubiquinone Q-10 as the predominant respiratory lipoquinone, a fatty acid profile with C18 : 1ω7c (62.6 %) and C19 : 0 cyclo ω8c (14.2 %) as the major components, a polar lipid profile with phosphatidylglycerol, phosphatidylethanolamine, phosphatidylcholine, phosphatidylmonomethylethanolamine, diphosphatidylglycerol and unknown aminolipids AL1 and AL2 as major polar lipids and spermidine and putrescine as the predominant polyamines also supported the affiliation of strain MJ11T to the genus Ochrobactrum. The DNA–DNA relatedness between strain MJ11T and Ochrobactrum ciceri DSM 22292T was 29±7 %, clearly showing that the isolate constitutes a new genospecies. Strain MJ11T could be clearly differentiated from its closest neighbours on the basis of its phenotypic, genotypic and chemotaxonomic features. Therefore, strain MJ11T represents a novel species of the genus Ochrobactrum, for which the name Ochrobactrum daejeonense sp. nov. is proposed. The type strain is MJ11T ( = KCTC 22458T = JCM 16234T).